EFFICACY OF INORGANIC SALTS AGAINST POTATO LATE BLIGHT - Bhat, M Narayana; Rani, Anju; Singh, B P (Potato Journal, 2013)
: Eighteen inorganic salts were evaluated for control of late blight. In detach leaf test, cupric sulphate (0.25%) and zinc sulphate (0.5%) were completely inhibitory to the pathogen. Aluminium chloride(0.5%) was also effective. All the three salts were also effective in controlling late blight at whole plant level.